Fenología y ciclo de vida del alga Gracilariopsis tenuifrons (Gracilariaceae) en Sucre, Venezuela - Brito, Leonor (2005)
Fenology and life cylce of Gracilariopsis tenuifrons (Gracilariaceae) at Sucre, Venezuela. The aim of this work was to determine the frequency of different reproductive phases and to induce the germination of spores from tetrasporic and cystocarpic Gracilariopsis tenuifrons from Chacopata and La Peña, Venezuela, under controlled laboratory conditions (temperature 22 ± 1ºC, 12L:12D photoperiod, salinity of 36 ± 1 PSU and irradiance of 269 μE m-2 s-1). Tetrasporic individuals dominated numerically over gametophitic individuals. The proportion of vegetative algae was very low. Only cystocarpic algae were collected and the spermatangia were absent. Sporulation, germination and formation of algae suggest that they present a Polysiphonia-type life cycle. Algae with reproductive structures were not obtained in the laboratory,